The Effect of Ephedrine on Fetal Outcome in Treatment of Maternal Hypotension Caused by Spinal Anesthesia During Cesarean Section - Fardin Yousefshahi; Fatemeh Davari Tanha; Mahbod Kaveh; Roghayeh Hamidian; Khosro Barkhordari (Tehran University of Medical Sciences, 2010)
Objective: To compare maternal complications and labor outcome in obese and non-obese women. Materials and methods: It is a retrospective comparative study conducted at the Department of obstetrics and gynecology, Unit 1, Civil Hospital, Karachi from December 2008 to December 2009. A sample size of 220 gravid women is selected by Non Probability Convenience sampling technique. In these 110 obese women as cases was compared with 110 non-obese women as controls, booked at <20 weeks of gestation. Data were collected regarding maternal complication, mode of delivery and neonatal outcome by trained medical officers. Data were entered and analyzed by SPSS version 11.0 through descriptive analysis, chi-square test  and independent sample t test. The p-value of <0.05 was considered significant. Results: Pregnancy induced hypertension was present in 9 (8.2%) women in control group and 21 (19.1%) in cases (p=0.01). Gestational diabetes was seen in one (0.9%) in control compared to 8 (7.3%) in obese women (p=0.01). Obese women were found to be at increased risk of caesarean section [17 (15.5%)  Vs. 39 (35.4%), p=0.002]. Apgar score at 1 and 10 minute were lower in cases compared to controls (p=0.0001). Conclusion: Obese women are at increased risk of pregnancy induced obesity and associated with an increased risk of hypertension, gestational diabetes mellitus, thromboembolic disease and urinary tract infection.